Gene expression profiling impacts treatment decision making in newly diagnosed multiple myeloma patients in the prospective PROMMIS trial. Issue 3 (11th May 2021) - Biran, Noa; Dhakal, Binod; Lentzsch, Suzanne; Siegel, David; Usmani, Saad Z.; Rossi, Adriana; Rosenbaum, Cara; Bhutani, Divaya; Vesole, David H.; Rodriguez, Cesar; Nooka, Ajay K.; van Rhee, Frits; et al.
Abstract: Multiple myeloma (MM) is a heterogeneous hematologic malignancy associated with several risk factors including genetic aberrations which impact disease response and survival. Thorough risk classification is essential to select the best clinical strategy to optimize outcomes. The SKY92 molecular signature classifies patients as standard‐ or high‐risk for progression. The PRospective Observational Multiple Myeloma Impact Study (PROMMIS; NCT02911571) measures impact of SKY92 on risk classification and treatment plan. Newly diagnosed MM patients had bone marrow aspirates analyzed for SKY92. Physicians completed a questionnaire for each patient capturing risk classification, hypothetical treatment plan, and physician confidence in the treatment plan, before and after unblinding SKY92. One hundred forty seven MM patients were enrolled. Before unblinding SKY92, physicians regarded 74 (50%) patients as clinical standard‐risk. After unblinding SKY92, 16 patients were re‐assigned as high‐risk by the physician, and for 15 of them treatment strategy was impacted, resulting in an escalated treatment plan. For the 73 (50%) clinical high‐risk patients, SKY92 indicated 46 patients to be standard‐risk; for 31 of these patients the treatment strategy was impacted consistent with a de‐escalation of risk. Overall, SKY92 impacted treatment decisions in 37% of patients ( p < 0.001). For clinical decision‐making, physicians incorporated SKY92, and the final assigned clinical risk was in line with SKY92 for 89% of patients. Furthermore, SKY92 significantly increased the confidence of the physicians' treatment decisions ( p < 0.001). This study shows potential added value of SKY92 in MM for treatment decision making.